Sight-saving antibiotic - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
There is new hope in the fight against river blindness, caused by parasites burrowing below the skin and releasing millions of offspring throughout the body. Scientists have found that it is, in fact, the worms cargo of Wolbachia bacteria that...